A new species of leaf fish, Nandus andrewi (Teleostei: Perciformes: Nandidae) from northeastern India - Ng, Heok Hee; Jaafar, Zeehan (Zootaxa, 2008)
Nandus andrewi sp. nov. is described from the Ichamati River in northeastern India. It differs from all congeners in having a bluish white (vs. mottled brown) body in life, and a combination of the following characters: body depth 24.3– 29.1% SL, pectoral fin length 15.1–18.5%, pelvic fin length 16.2–18.9% SL, eye diameter 18.3–21.7% HL, a dark spot on the caudal peduncle, and 45–52 lateral-line scales. A key to the species of Nandus is also provided.